Landscapes Of Urban Memory : The Sacred and the Civic in India's High-Tech City - Srinivas, Smriti (Book collections on Project MUSE., 1997)
The city of Bangalore has become a center for high-technology research and production, the new?Silicon Valley? of India. It is also the site of the very popular annual performance called the?Karaga? dedicated to Draupadi, the polyandrous wife of the her.